Whither to, the judiciary in Zimbabwe? A critical analysis of the human rights jurisprudence of the Gubbay and Chidyausiku Supreme Court benches in Zimbabwe and comparative experiences from Uganda - Jjuuko, Frederick W. (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2005.